Atratividade e palatabilidade de dietas contendo hidrolisados proteicos de frango com inclusão de amido, maltodextrina e levedura para alevinos de tambaqui (Colossoma macropomum) - Freitas, Katianne Santos (2023)
The study was carried out with the aim of determining the attractiveness and palatability of tambaqui (Colossoma macropomum) fingerlings fed with diets containing hydrolyzed feather protein or hydrolyzed chicken protein with starch, maltodextrin or yeast. For the test, ten fingerlings with an average weight of 16.5 ± 4.35g were used, distributed in ten aquariums with a useful volume of twenty liters. Five diets were formulated, as follows: 1-fish meal ((FPE) - positive control diet); 2-hydrolyzed feather protein (PHP); 3-hydrolyzed chicken protein with starch (PHFA60%); 4-hydrolyzed chicken protein with maltodextrin (PHFM60%); and 5-hydrolyzed chicken protein with yeast (PHFL60%). The fish were fed five times a day, at 8:00 am, 10:30 am, 1:00 pm, 3:30 pm and 6:00 pm, for a period of ten days, offering 20 pellets per feeding, which were filmed for three minutes. The experiment evaluated the attractiveness and palatability of the diets, observing the following feeding behaviors: time to capture the first pellet (seconds), number of pellet rejections after capture, number of approaches without capturing the pellet and number of pellets consumed. The attractiveness and palatability index was obtained by the equation: IP = ((R-C) /(R+C)) *100. Data were submitted to parametric analysis of variance (ANOVA), and Tukey's multiple comparison test was also performed, with a significance level of 5%. The diets showed IP ranging from 0.14 to -5.05. The diet containing hydrolyzed feathers (PHP) had the best PI of 0.14%, the lowest number of approximations without pellet capture and the highest pellet consumption, 69.80%, when compared to the control treatment (FPE). However, the evaluated parameters and the palatability index showed no significant difference (p> 0.05). Thus, the evaluated diets can be used in diets for tambaqui (Colossoma macropomum), without altering palatability and feeding behavior.